2020
DOI: 10.1089/apc.2020.0114
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Internalized Stigma and HIV Health Outcomes in Individuals New to HIV Care: The Mediating Roles of Depression and Treatment Self-Efficacy

Abstract: There is limited research on the effects of stigma on health outcomes among new-to-HIV care individuals. We examined the effect of changes in internalized stigma over time on health behaviors and outcomes such as viral suppression, antiretroviral therapy (ART) adherence, and visit adherence among new-to-HIV care individuals. We also analyzed the mediating effects of adherence self-efficacy and depressive symptoms in these associations. Participants were 186 persons living with HIV who initiated care at four HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…Several studies from Asia, Africa, Australia, the Caribbean, and the United States have shown a correlation between internalized stigma and depression among PLHIV [16,[21][22][23][24][25][26][27][28][29][30]. From a cognitive theory perspective, depression is defined by people's dysfunctional negative beliefs about themselves, their life experience, their future, and the world in general [31], while internalized stigma entails accepting society's negative attitudes and feelings regarding PLHIV and applying them to oneself [32].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies from Asia, Africa, Australia, the Caribbean, and the United States have shown a correlation between internalized stigma and depression among PLHIV [16,[21][22][23][24][25][26][27][28][29][30]. From a cognitive theory perspective, depression is defined by people's dysfunctional negative beliefs about themselves, their life experience, their future, and the world in general [31], while internalized stigma entails accepting society's negative attitudes and feelings regarding PLHIV and applying them to oneself [32].…”
Section: Introductionmentioning
confidence: 99%
“…Literature on HIV-related stigma finds its roots in the early work of Erving Goffman (1963), 12 who defined stigma as “the discrediting of individuals based on an undesirable attribute.” (p3) Today, HIV-related stigma is characterized by various forms of stigma that can be encountered by PLHIV, including public stigma and self-stigma (also referred to as internalized stigma). 13 , 14 Public stigma entails the negative beliefs held in society about HIV, negative emotional reactions such as anger or disgust, and negative behaviors such as avoidance or abuse toward PLHIV. 15 , 16 Public stigma can be perceived as well as experienced (i.e., discrimination or enacted stigma).…”
Section: Introductionmentioning
confidence: 99%
“…Stigma is linked to negative psychological, social, and physical health outcomes (e.g., depression, anxiety, lower self-esteem, disclosure concerns, reduced social support, sexual problems, sleeping difficulties, and poorer general health) across different countries and key populations including individuals with a migration background, men who have sex with men (MSM), women, and people with substance use dependence. 8 , 13 , 14 , 19 , 22–30 …”
Section: Introductionmentioning
confidence: 99%
“…7 Given its potential to combat HIV stigma, U=U messaging may promote a status-neutral approach to ending the HIV epidemic as HIV stigma is a structural barrier to HIV testing [10][11][12][13][14] and pre-exposure prophylaxis (PrEP) uptake [15][16][17][18] among people without HIV and to care and treatment among PWH. [19][20][21][22][23] Given the recency of U=U, however, empirical data examining the role of U=U in dismantling HIV stigma are scarce. In their HIV Stigma Framework, Earnshaw and Chaudoir proposed that HIV stigma affects both PWH and people without HIV through different mechanisms and can serve as an impediment to HIV prevention and treatment efforts.…”
Section: Introductionmentioning
confidence: 99%